Values in the university education of the xxi century. Reflections on plurality, freedom, otherness and tolerance (2021)
It is never irrelevant to remember that in its historical tradition the university has faced, since its inception in Middle Ages Europe, a struggle in permanent tension against various factors of power, for the recognition and affirmation of its identity. Those values that belong to students and teachers of all times and that are synthesized within the concept of autonomy and the love of knowledge. Values that are the frame of reference that allows us to be tolerant in the face of discrepancies or dissimilar points of view and above all to develop a sense of responsibility and duty; which entails the construction of a freedom that is enriched from alterity as a dialectic that involves the development of continuous learning and that makes use of the necessary presence of a plurality of individuals who mutually recognize and respect each other from each of their differences . We propose to turn mainly to the reflections of H. Arendt to explain the foundations of the concepts of plurality, freedom, otherness and tolerance, applied in the context of university coexistence that calls teachers and disciples to share the dream and experience of building in the space of the academies “the world of human affairs”.